Implikasi Istri Sebagai Pelaku Bisnis Online Terhadap Pemenuhan Keharmonisan Keluarga - Rachmat Lukman Hakim, R Arrazy (Al-Hukkam: Journal of Islamic Family Law, 2021)
As happened in Medono Village, Pekalongan City, which has encouraged the role of women not only to revolve around household activities but also to do online business. In Medono Village, Pekalongan City, there are many wives who play a role in doing online business. The purpose of this study is to explain the reasons why women in the Medono sub-district, Pekalongan City do Online Business and its implications for Family Harmony. This type of research is field research with a qualitative approach. The data sources are primary and secondary data, with the subject of a wife who has an online business and its implications for family harmony. Collecting data by interview, observation and documentation. The technique of analyzing qualitative data is an interactive model, using gender and feminist theories about justice and gender equality. The results of this study concluded that the reasons that caused the wife in the Medono sub-district, Pekalongan City to do online business, were due to several factors, namely: independence factors, economic factors, educational factors, self-actualization factors, social factors, religious factors, opportunity factors, health factors, factors progress in the field of science and technology, women's empowerment factors.